Pengaruh Metode Fami Bisyauqin terhadap Bacaan Al Qur’an Binnazar Santri Pondok Pesantren Salafiyah Kediri - Inayah Khulatifah; Miftahuddin (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The effort to find the effect of the fami bisyauqin method on the quality of reading the Qur'an is the focus of this research. The background of this concern is to measure the quality of reading the Qur'an by students at the Salafiyah Islamic Boarding School in Kediri City, which so far has never been done. Other tahfidz Islamic boarding schools have measuring tools for evaluation and reference in determining future Qur'an learning strategies. This research was conducted by distributing questionnaires with a sample of 28 students. The method of analysis uses non-parametric statistics Kendall tau formula. The results state that the correlation between the reading value of the Qur'an binnazar santri with the fami bisyauqin method is very low; this is because the students only focus on reading the Qur'an without knowing the method used when reading the Qur'an with the fami bisyauqin method.